Biogenic selenium nanoparticles: characterization, antimicrobial activity and effects on human dendritic cells and fibroblasts. Issue 6 (20th June 2016) - Cremonini, Eleonora; Zonaro, Emanuele; Donini, Marta; Lampis, Silvia; Boaretti, Marzia; Dusi, Stefano; Melotti, Paola; Lleo, Maria M.; Vallini, Giovanni
Summary: Tailored nanoparticles offer a novel approach to fight antibiotic‐resistant microorganisms. We analysed biogenic selenium nanoparticles (SeNPs) of bacterial origin to determine their antimicrobial activity against selected pathogens in their planktonic and biofilm states. SeNPs synthesized by Gram‐negative Stenotrophomonas maltophilia [Sm‐SeNPs(−)] and Gram‐positive Bacillus mycoides [Bm‐SeNPs(+)] were active at low minimum inhibitory concentrations against a number of clinical isolates of Pseudomonas aeruginosa but did not inhibit clinical isolates of the yeast species Candida albicans and C. parapsilosis . However, the SeNPs were able to inhibit biofilm formation and also to disaggregate the mature glycocalyx in both P. aeruginosa and Candida spp. The Sm‐SeNPs(−) and Bm‐SeNPs(+) both achieved much stronger antimicrobial effects than synthetic selenium nanoparticles (Ch‐SeNPs). Dendritic cells and fibroblasts exposed to Sm‐SeNPs(−), Bm‐SeNPs(+) and Ch‐SeNPs did not show any loss of cell viability, any increase in the release of reactive oxygen species or any significant increase in the secretion of pro‐inflammatory and immunostimulatory cytokines. Biogenic SeNPs therefore appear to be reliable candidates for safe medical applications, alone or in association with traditional antibiotics, to inhibit the growth of clinical isolates of P. aeruginosa or to facilitate the penetration of P. aeruginosa and Candida spp. biofilms by antimicrobial agents. Abstract : Biogenic SeNPs exhibited a higher antimicrobial and biofilm eradicating activity than chemically synthesized SeNPs. Moreover, they did not show toxicity against fibroblasts and dendritic cells.